2022
DOI: 10.1186/s12887-022-03680-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with healthcare-seeking behavior for symptomatic acute respiratory infection among children in East Africa: a cross-sectional study

Abstract: Background Although there has been promising progress in the reduction of child mortality from ARI, the magnitude is high yet, especially in East Africa. Since mothers/guardians decide upon the type and frequency of healthcare services for children, their good healthcare-seeking behavior could prevent acute respiratory infections (ARI) related mortality and morbidity. This study aimed to investigate the pooled prevalence and factors associated with healthcare-seeking behavior of children younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…These results are similar to those found by Chilot et al, who obtained a prevalence of 64.4% for East Africa from 2012 to 2020 [18].On the other hand, lower prevalences were reported by Demissie et al in Ethiopia in 2019 (58.7%) and Nshimiyimana et al in Uganda in 2016 with a prevalence of 40.3% for a sample of 13493 children under 5 years of age [19] [20].…”
Section: ) Prevalence Of Arisupporting
confidence: 89%
“…These results are similar to those found by Chilot et al, who obtained a prevalence of 64.4% for East Africa from 2012 to 2020 [18].On the other hand, lower prevalences were reported by Demissie et al in Ethiopia in 2019 (58.7%) and Nshimiyimana et al in Uganda in 2016 with a prevalence of 40.3% for a sample of 13493 children under 5 years of age [19] [20].…”
Section: ) Prevalence Of Arisupporting
confidence: 89%
“…Among women who had attended secondary education, acute respiratory infection was reduced compared to that in women who had no education. This nding is supported by studies conducted in Ethiopia [28,29], Bangladesh [30], and Ghana [31]. Many scholars have revealed that educated women are aware of ARI symptoms and exhibit early healthcare-seeking behaviors.…”
Section: Discussionmentioning
confidence: 57%
“…Many scholars have revealed that educated women are aware of ARI symptoms and exhibit early healthcare-seeking behaviors. Furthermore, it might be attributable to the fact that education can enhance mothers' and caregivers' healthcare-seeking behaviors for children with ARI symptoms [29]. Moreover, education enables mothers to be informed about how to access and use information on children's health and make health decisions for their children [28,31].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of this study was seeking healthcare for children under the age of five who had ARI symptoms in the two weeks preceding the interview. Seeking medical care was defined as seeking treatment from any health facility, excluding treatment from a traditional practitioner, by their mother/caregiver in the two weeks preceding the survey, and coded as “1”, otherwise “0” [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%